ANALISIS PENDAPATAN USAHATANI WORTEL DI DESA SUBAN AYAM KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Indah Fitria (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2018)
The purpose of this study is to find out how much income of carrot farming in the research area and to know the influence between the land area of education, age and the number of family dependent on the income of carrot farming in the research area. Based on the analysis that has been done obtained the average income of wortel farming system in sub chicken village is Rp. 3.928.380,-/Ut. This means that farmers acceptancet can cover all costs incurred during the farming production activities. The size of the land of educational age and the number of family dependents simultaneously significantly affect the income of carrot farming and partially significant effect is the area of age and the number of dependents of the family.